Epinephrine-Induced Aggregation of Rabbit Platelets Refractory to ADP - Keraly, C Lalau; Kinlough-Rathbone, R L; Mustard, J F (Thrombosis and Haemostasis, 1985)
The mechanisms involved in platelet aggregation induced by epinephrine are unclear. Although epinephrine does not aggregate washed rabbit platelets, platelets made refractory to ADP will aggregate in response to epinephrine in the presence of ADP. We have examined whether the mechanism(s) by which epinephrine induces aggregation of refractory platelets involves fibrinogen binding and Ca2+ association. With normal platelets, ADP causes aggregation, fibrinogen binding and Ca2+ association in a medium containing 0.2 mM 45Ca2+. After 3 min of incubation with ADP, fibrinogen dissociates from platelets, but 45Ca2+ does not. Epinephrine alone does not cause aggregation, fibrinogen binding or 45Ca2+ association. Platelets that are refractory to ADP do not aggregate and bind fibrinogen upon addition of ADP, but aggregate and bind fibrinogen in response to epinephrine, provided ADP is still present. These effects of epinephrine are mediated by the α-adrenergic receptor since they are blocked by phentolamine or verapamil and potentiated by propranolol. However, epinephrine-induced aggregation of platelets refractory to ADP does not involve further detectable increase in the amount of 45Ca2+ associated with the platelets.
Keywords: Platelet aggregation; Refractory platelets; Epinephrine